Spectrum of renal biopsies; a three-year data from a tertiary care centre of eastern India - Chetan Mahajan; Vaibhav Tiwari; Smita Subhash Divyaveer; Malagouda R Patil; Avinandan Banerjee; Vishnuvardhan Bagur; Umesh Dubey; Koushik Battacharjee; Sandeep Saini; Tanima Das Bhattacharya; Arpita Raychaudhury; Sanjay Dasgupta; et al. (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Biopsy registries are important in studying the frequency of kidney diseases, their trends over time and allow comparison of data from different geographical regions. Objectives: We report the spectrum of biopsy-proven glomerular and tubular diseases in a single centre in Eastern India. Patients and Methods: Medical records of 1293 patients with biopsy-proven glomerular diseases (GDs) and tubular diseases over a period of three years (March 2013 to March 2016) were retrospectively analysed. All biopsy specimens were examined by the same pathologist with light and immunofluorescence microscopy. Electron microscopic (EM) analysis was performed only in selected cases. Histologic spectrum of various GDs was studied along with its correlation with the clinical and laboratory parameters. Results: The clinical diagnosis was nephrotic syndrome (NS) in 820 (63.41%), rapidly progressive glomerulonephritis in 194 (15.2%), asymptomatic urinary abnormalities (AUA) in 108 (8%), acute kidney injury (AKI)/acute nephritic syndrome in 118 (9.3%), and macroscopic hematuria (MH) in 3 (0.43%) patients. Male: Female ratio was 0.95. Around 22.42% were < 18 years, 72.2% were between 18to 59 years, and 5.3% were ≥ 60 years of age. The most common GD overall as well as primary glomerular disease (PGD) was minimal change disease (MCD) (21.6 and 83.44%). Secondary GD was present in 20.87%; most common being lupus nephritis (84.58%). Among the NS, the most common GD was MCD (33.17%), followed by FSGS (17.56%), membranous nephropathy (MN) (13.90%), lupus nephritis (LN) (9.39%), IgA-nephropathy (0.49%), and MPGN (7.32%). Thrombotic microangiopathy (TMA) constituted 24.6% of AKI presentation particularly common in pregnancy. Diffuse proliferative glomerulonephritis (DPGN) with severe renal dysfunction was present in 14% of elderly patients. Conclusion: The spectrum of GD varies according to the area of study and changes over time. Some entities which have not been reported earlier from this region that are uncommon but are significant were pregnancy associated TMA, C3 glomerulopathy (C3G) and DPGN in adults.